The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1128/jb.182.22.6358-6365.2000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mRNA Transcripts and Active Transcription in Persistent Mycobacterium tuberculosis Induced by Exposure to Rifampin or Pyrazinamide

Abstract: Mycobacterium tuberculosis can persist in an altered physiological state for many years after initial infection, and it may reactivate to cause active disease. An analogous persistent state, possibly consisting of several different subpopulations of bacteria, may arise during chemotherapy; this state is thought to be responsible for the prolonged period required for effective chemotherapy. Using two models of drug-induced persistence, we show that both microaerophilic stationary-phase M. tuberculosis treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(145 citation statements)
references
References 31 publications
(30 reference statements)
10
134
1
Order By: Relevance
“…Furthermore, the differential sensitivity of σ R -RNAP and σ HrdB -RNAP to Rif might have important implications for how M. tuberculosis responds to Rif treatment. Transcriptional activity has been detected in M. tuberculosis even following extensive treatment with Rif, including heat-induced expression of DnaK (Hu et al, 2000). It is known from other work that DnaK is controlled by the σ R homologue, σ H , in M. tuberculosis (Raman et al, 2001), which suggests that like σ R -RNAP, σ H -RNAP is resistant to Rif.…”
Section: Occurrence Of Rbpa In Pathogenic Actinomycetesmentioning
confidence: 88%
“…Furthermore, the differential sensitivity of σ R -RNAP and σ HrdB -RNAP to Rif might have important implications for how M. tuberculosis responds to Rif treatment. Transcriptional activity has been detected in M. tuberculosis even following extensive treatment with Rif, including heat-induced expression of DnaK (Hu et al, 2000). It is known from other work that DnaK is controlled by the σ R homologue, σ H , in M. tuberculosis (Raman et al, 2001), which suggests that like σ R -RNAP, σ H -RNAP is resistant to Rif.…”
Section: Occurrence Of Rbpa In Pathogenic Actinomycetesmentioning
confidence: 88%
“…Alternatively, nonreplicating cells may contain some unresolved FtsZ-associated structures. Recently it has been shown that dormant cultures of M. tuberculosis exhibit both transcriptional and metabolic activity (Hu et al, 2000). It is unknown whether such transcriptional activity extends to the ftsZ gene.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, noncolony-forming Mtb were phenotypically tolerant to combination chemotherapy, and their viability was demonstrated by their ability to cause relapse. More recent studies of cfu-negative organ samples from Mtb-infected mice treated with other drug regimens suggested the presence of DD Mtb by detection of Mtb mRNA transcripts (49) or demonstrated the presence of DD Mtb by recovery of Mtb in liquid medium supplemented with CF from log-phase Mtb (50). The ability to use non-agar-based culture methods to grow DD Mtb from mice (22) or human sputum (13,14) makes the term "nonculturable" inappropriate.…”
Section: Discussionmentioning
confidence: 99%